Remittances and Happiness of Migrants and Their Home Households: Evidence Using Matched Samples - Joarder, Munim; Harris, Mark N.; Dockery, Alfred Michael (Routledge, 2016)
This paper explores how remittances influence happiness among migrants and their households of origin. It is based on a novel data set of matched samples of Bangladeshi migrant households (living in the UK and Malaysia) and their origin families in Bangladesh. Empirical findings suggest that remittances play a significant role in stimulating migrants’ happiness. We also find that the households of origin’s life satisfaction not only depends on receiving remittances from the emigrants, but also other factors such as number of migrants from the household living abroad and the migrants’ country of destination.